The University in the digital society: between the analogic heritage and the socialization of knowledge - P. Rivera-Vargas; C. Cobo Romaní (Universitat Politècnica de València, 2019)
Digital technologies are tools that offer to universities spaces for growth, but also generate or amplify both classic and contemporary problems. Therefore, beyond the expectations, these can reinforce the existing gaps. The rhetoric pro society of knowledge, put the university at the center of the debate assigning a privileged position. These would play a key role in the digital era to produce relevant knowledge and to train new generations of workers. However, the multiple inertias that have been orienting the financial market to an important part of the production and university offer, have enabled certain economic sectors to take advantage of this position of relevance. In this way, to be able to squeeze (or devour) as much as possible the ethos of the university under a rationale of total commercialization, characterized by: excessive growth in enrolment; productivity rankings; Compulsory practices of dissemination of scientific knowledge; accumulation practices of the best: students, teachers, facilities, etc. Considering this scenario, in this article we try to answer the following question: What challenges arise in the digital society when it comes to rethinking the universities of the 21st century? This question is approached from a theoreticalreflexive review of relevant historical and contemporary antecedents. As a result of this analytical exercise, the complexities are recognized, but at the same time the opportunities that emerge in the digital society for one of the most traditional, conservative and, at the same time, relevant institutions of the history of knowledge in humanity.